The Alignment of the Final Letters in the Alala Book by Sheikh Al-Zarnuji: Balaghah Analysis Study - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
The Alala Book is a small book containing a collection of advice poems in the Ta'lim Mutaa'llim book by Sheikh Al-Zarnuji. This book is widely studied in various educational institutions, especially Islamic boarding schools. The book of Alala has its charm because it contains poems that have a beauty value in terms of the beauty of the lafadz, including poetry. This study aims to discover what types of poetry are included in the Alala book. With the science of poetry, researchers can determine the final letters in the two fashilah and select the kind of poems. The method used by the researcher in this study is a qualitative method with a literature study approach, namely by describing the data by finding the final letters contained in two or more fashilah to determine what types of poetry are included in the Alala book. The results of this study conclude that poetry is divided into three styles, including mutharraf, murashsha' and mutawazi poetry. The number of poems in this book is 17 poems consisting of seven mutharraf poems, one murashsha verse, and nine mutawazi poems.